THE EFFECT OF PROFITABILITY, CAPITAL STRUCTURE, AND ASSET GROWTH ON DIVIDEND POLICY (Case study on LQ45 companies listed on the IDX for the 2019-2024 period) - Puspitasari, Diyah; Sunarto, Sunarto (Journal of Industrial Engineering & Management Research, 2026)
This study aims to examine the influence of Profitability, Capital Structure, and Growth on Dividend Policy. The data used in this study are secondary data taken from the issuer's financial statements listed on the IDX for the 2019-2024 period. The sample was used by 114 companies. The sample sampling technique uses the Purposive sampling method. This study uses multiple linear regression analysis with the SPSS program. The results of this study show that profitability does not have a significant effect on dividend policy, capital structure has a negative effect on dividend policy, and asset growth has a positive effect on dividend policy.